Sistem Pembagian Waris Adat Lampung Pepadun Perspektif Maqâshid Al-Syarî’ah Dan Al-‘Urf - Chanifan Ihyarangga Sudarmaji; Bela Arlinda Pratiwi (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
The presence of Islam which is proven to be able to acculturate with customs and culture in Indonesia has brought a shift in people's behavior. Changes in people's behavior are not instantaneous, but shift along with the rhythm of the movement of civilization progress. The same applies to inheritance issues in Indonesia. Although the majority of Muslims have followed religious guidance in its implementation, the reality on the ground is that community groups still use customary rules. As done by the indigenous people of Lampung Pepadun in the South Menggala Village, Menggala District, Tulang Bawang Regency, they still maintain the distribution of inheritance with the Patrilineal system or what the community calls the single heir system, namely the male mayorat. This research is a field research with a case study approach. Data analysis was carried out by means of data reduction, data presentation, conclusion drawing and verification. The purpose of this study is to find out the Patrilineal system carried out by the indigenous people of Lampung Pepadun in the review of Maqâshid Al-Syarî'ah and al-'Urf. The results showed that the inheritance distribution system which was carried out based on the customs of the Lampung Pepadun community by applying the Patrilineal inheritance system, contained the al-'Urf aspect. From the perspective of Maqâshid Al-Syarî'ah, the value of benefit in implementing an inheritance distribution system based on the customs of the Lampung Pepadun community in South Menggala Village, Menggala District, Tulang Bawang Regency is not fully in accordance with Maqâshid Al-Syarî'ah, which is only able to maintain religion and maintain property. Meanwhile, for the rest, namely maintaining the soul, maintaining the mind and maintaining offspring for girls or boys other than the sole heir, it still depends on the awareness of the sole heir regarding his responsibilities as a substitute for parents.